Treatment of high strength industrial wastewater using extended aeration-immersed microfiltration (EAM) process - Megat Mohd Noor, Megat Johari; Nagaoka, Hiroshi; Aya, Hidenori (2002)
Fully submerged laboratory scale hollow fiber microfiltration module was used to treat a food industry wastewater in Malaysia. Permeate extraction was carried out continuously under a suction pressure not exceeding 0.9 bar. The module is aerated from beneath the microfiltration module to provide the crossflow effect and the oxygen requirement for the biological process. Active sludge from activated sludge plant at the factory was used in the start-up with a food/microorganisms (F/M) ratio of about 0.6, which later reduced further with time to 0.13 subject to the increase in the mixed liquor suspended solids (MLSS) and the permeate extraction rate. Primary effluent with chemical oxygen demand (COD) ranged between 1500 and 3000 mg/l was used in the study. MLSS of over 5500 mg/l were reached after nearly three month of filtration run. Permeate COD and turbidity reduction of over 97% and 99% respectively, were achieved. Dark streaks that formed on the inner side of the membrane surface are responsible for the declining permeate turbidity in the second month of operation since the membrane nominal size remains relatively unchanged.